Host cell factors as antiviral targets in arenavirus infection - Linero, Florencia Natalia (2012)
Among the members of the Arenaviridae family, Lassa virus and Junin virus generate periodic annual outbreaks of severe human hemorrhagic fever (HF) in endemic areas of West Africa and Argentina, respectively. Given the human health threat that arenaviruses represent and the lack of a specific and safe chemotherapy, the search for effective antiviral compounds is a continuous demanding effort. Since diverse host cell pathways and enzymes are used by RNA viruses to fulfill their replicative cycle, the targeting of a host process has turned an attractive antiviral approach in the last years for many unrelated virus types. This strategy has the additional benefit to reduce the serious challenge for therapy of RNA viruses to escape from drug effects through selection of resistant variants triggered by their high mutation rate. This article focuses on novel strategies to identify inhibitors for arenavirus therapy, analyzing the potential for antiviral developments of diverse host factors essential for virus infection.